2014
DOI: 10.1002/2013jd020621
|View full text |Cite
|
Sign up to set email alerts
|

Variability in surface meteorology and air‐sea fluxes due to cumulus convective systems observed during CINDY/DYNAMO

Abstract: This study examines the variability in surface meteorological parameters and air-sea heat fluxes due to cold pools emanating from cumulus convective systems observed over the tropical Indian Ocean in November 2011. In particular, this study focuses on convective systems that are spatially smaller than mesoscale convective systems in a southeasterly trade wind environment. Composite analyses of convectively active periods show an increase in the sensible heat flux by 15-20 W m À2 that is primarily attributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 28 publications
(71 reference statements)
7
33
0
Order By: Relevance
“…3) is primarily explained by wind variability. Other studies have also found LHFLX anomalies to be primarily wind driven (Jones and Weare 1996;Maloney and Esbensen 2007;AM08;Grodsky et al 2009;Yokoi et al 2014). Thermodynamic variability, on the other hand, largely opposes or damps the positive relationship between intraseasonal LHFLX anomalies and precipitation anomalies (i.e., Figs.…”
Section: Sensitivity Of Lhflx To Wind Vs Air-seamentioning
confidence: 82%
See 2 more Smart Citations
“…3) is primarily explained by wind variability. Other studies have also found LHFLX anomalies to be primarily wind driven (Jones and Weare 1996;Maloney and Esbensen 2007;AM08;Grodsky et al 2009;Yokoi et al 2014). Thermodynamic variability, on the other hand, largely opposes or damps the positive relationship between intraseasonal LHFLX anomalies and precipitation anomalies (i.e., Figs.…”
Section: Sensitivity Of Lhflx To Wind Vs Air-seamentioning
confidence: 82%
“…In more recent findings, Sobel et al (2014) showed vertical advection discharges column MSE at a rate of 10 % -20 % of precipitation at the peak of the CINDY/ DYNAMO (i.e., Cooperative Indian Ocean Experiments on Intraseasonal Variability in the Year 2011; Dynamics of the MJO) field campaign (Yokoi et al 2014;Moum et al 2013). We note that in both Yu et al (1998) and Sobel et al (2014) precipitation was converted to energy units to compute the ratio of MSE discharge from vertical motions associated with convection.…”
Section: Brief Background On Wishe and Moisture Mode Theorymentioning
confidence: 96%
See 1 more Smart Citation
“…Intensive observations were conducted over the Indian Ocean (hereafter, IO) during the period from 1 October 2011 to 15 January 2012, and a large amount of high-quality data was collected (Ciesielski et al 2014a;Deng et al 2014;Feng et al 2014;Moum et al 2014;Y13). The observations captured many important processes that would be key to a complete understanding of the MJO, such as (1) the deep moistening which led to MJO convective initiation Johnson and Ciesielski 2013;Johnson et al 2015;Y13), (2) the evolution of populations of different cloud types in each stage of the MJO (Bellenger et al 2015;Feng et al 2014;Powell and Houze 2013;Ruppert and Johnson 2015;Zuluaga and Houze 2013;Xu and Rutledge 2014), and (3) the sub-daily to seasonal upper ocean variations Moum et al 2014;Seiki et al 2013;Yokoi et al 2014;Y13).…”
Section: Introductionmentioning
confidence: 99%
“…Convection from hot horizontal surfaces has many applications in different fields of study including heat pipes [1], earth mantle convection [2], and formation of sea winds [3]. Convection from hot horizontal surfaces has many applications in different fields of study including heat pipes [1], earth mantle convection [2], and formation of sea winds [3].…”
Section: Introductionmentioning
confidence: 99%